PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE INDEX CARD MATCH (ICM) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsTI BATANG KABUNG PADANG TAHUN PELAJARAN 2013/ 2014 - Fauziyah, Yossy; Husna, Husna; Febriana, Rina (Pendidikan Matematika, 2013)
This research is motivated because of low grade of the studentâs inability of solving a different problem with example and to undersatand the mathematical concepts of 8th grade students of MTsTI Batang Kabung Padang. The research purpose to determine whether studentâs understanding of mathematical concepts through the application of active learning strategies by using Index Card Match type is better than the studentâs understanding od mathematical concepts by using conventional learning in class VIII MTsTI Batang Kabung Padang Acedemic Year 2013/ 2014. This type of research is experimental research of experimental studies Against Random Subjects. Analysis technique use the one party t test by using MINITAB. Based on the analysis of data obtained P-value is Â smaller than , so it can be concluded that studentâs understanding of mathematical concept using active learning strategies Index Card Match type is better than the students understanding of mathematical conceps by using conventional learning in class VIII MTsTI Batang Kabung Padang.